Ein Verkehrsmittelwahlmodell für den Personenfernverkehr auf Basis von Verkehrswiderständen. - Norta, Manuel (My University, 2012)
Im Rahmen der Arbeit erfolgen die Entwicklung sowie die Validierung eines aggregierten aber dennoch den Reiseverlauf sehr feingranular abbildenden Verkehrsmittelwahlmodells für den Personenfernverkehr. Die Betrachtung erfolgt dabei stets auf eine Relation bezogen unter Berücksichtigung aller relevanten miteinander konkurrierenden Verkehrsmittel. Die in Abhängigkeit von der Relation stark differierenden Siedlungs- und Bevölkerungsstrukturen sowie die in den Untersuchungsräumen existierenden Verkehrsangebote werden somit umfassend abgebildet. Die Qualität dieser Verkehrsangebote wird auf der Basis einer präzisen Widerstandsformulierung beschrieben, deren Grundlagen die Angebotsparameter der betreffenden Angebote sowie die jeweiligen subjektiven nicht-linearen Bewertungen durch den das Angebot nutzenden Kunden darstellen. Einen wesentlichen Schwerpunkt der Betrachtungen stellen dabei die notwendigen Zu- und Abgängen zu/von den öffentlichen Verkehrsmitteln, die Komplexität von Systemwechsel und Umsteigen, die Nutzbarkeit von Reisezeitelementen und die außerplanmäßigen Wartezeiten dar, da diese Aspekte einen nicht unerheblichen Einfluss auf die Verkehrsmittelwahl haben. Anschließend wird ein Netzmodell entwickelt, welches sich an bestehenden Modellen orientiert und somit die Verwendung der an anderer Stelle vorgehaltenen soziodemographischen sowie siedlungsstrukturellen Datengrundlagen wesentlich vereinfacht. Die Erfordernis, die räumlich differenzierten Angebotsverhältnisse zusammenzufassen, wird mittels eines relationsbezogenen Mittelungsverfahren sichergestellt. In einem abschließenden Schritt werden die bislang vor allem auf Basis von Hypothesen entwickelten funktionalen Zusammenhänge mit Hilfe einer umfangreichen sowie feingranularen relationsspezifischen Reisendenerhebung validiert.

The work develops and validates a modal choice model which although aggregated nevertheless give a very fine-grained representation of the travel itinerary. The view taken is invariably relative to a route giving consideration to all relevant competing means of travel. The widely differing urbanisation and population structures depending on the route and the offered travels means existing in the investigated areas are thus comprehensively represented. The quality of these travel offers is described on the basis of a precise resistance formulation which is founded on the parameters of the offers in question and the respective subjective non-linear evaluations by the customers using that offer. The first step is to find a suitable modelling approach and a suitable method for de-veloping the necessary decision algorithms. The VIA resistance model is used in view of the necessity of delivering results quickly but which must be route-related and fine-grained. This means that the model only needs to be calibrated once and the sensitivity of reaction to measures is ensured. Due to the insufficient data basis in long-distance passenger traffic, it is necessary to recourse to a model development approach based on hypotheses. In the next step, the offer characteristics of the travel means and investigation area are quantified and the subjective non-linear evaluation functions established. An essential emphasis of this view are the necessary accesses and exits from the public transportation, the complexity of system change and changing carrier, the usability of travel time elements and the unscheduled waiting times because these aspects have a considerable influence on the selection of travel means. The necessity of summarising spatially differentiated offer situations is ensured by a route-related averaging method. In a final step, the functional interdependencies that used to be developed above all on the basis of hypotheses are now validated with the help of a comprehensive and route-specific traveller survey. The overall total functionality of the model is secured with the review of numerous very differently structured routes. With this model, a tool is available that makes it possible to calculate plausible results and travel means selection changes close to reality without prior surveys. The approach is mathematically viable despite its detailing.
Modal choice model for long-distance passenger services based on traffic resistances.
Keywords: Verkehr; Personenfernverkehr; Verkehrsplanung; Verkehrsnachfrage; Verkehrsverhalten; Verkehrsmittelwahl; Verkehrsmodell; Verkehrsangebot; Modal Split; Reisezeit